Privatisation and renationalisation: What went wrong in Bolivia's water sector? - Degol Hailu; Rafael Guerreiro Osório; Raquel Tsukada (International Policy Centre for Inclusive Growth (IPC-IG), 2009)
This paper investigates the concentration of access to safe water across income levels in Bolivia. In particular, it focuses on how privatisation has changed coverage, affordability and the concentration of access to water on the part of the poor. We compare the performance of cities in which the service was privatised (La Paz and El Alto) with a city in which it is managed as a cooperative (Santa Cruz de la Sierra) and one where the service is publicly provided (Cochabamba). We examine the pre- and post-privatisation periods. Close inspection of the household surveys reveals that access to water by low-income consumers increased in the periods when the service was provided under private concessions. Coverage has expanded significantly in the bottom quintiles of the population in the cities where water was privatised, and thus access to water is more equitable. The state, however, renationalised the water utility. What went wrong, then, in Bolivia's water sector? The answer is that the private concessionaire failed to meet the targets stipulated in the concession contract. The tariff increases required for full cost recovery eventually led to public outrage that forced the government to terminate the contract.
Keywords: L95; L33; L43; I39; 330; access to water; poverty; privatisation; utility regulation; Wasserversorgung; Privatisierung; Armut; Bolivien